The medium-term effect of oil price on current account, savings, and investment - Kok, Zi Cheng (2019)
Current account imbalances have grown for the past decades and thus garnered a lot of attentions from academics and policy makers alike. Past economic crises like the 1997 Asian Financial Crisis are caused by the accumulation of excessive external debts by countries with unsustainable current account deficits. Therefore, it is pertinent for countries to comprehend the myriad determinants of current account to better managed their current account. Oil, being one of the most commonly traded commodities, plays a non-negligible role in affecting country’s current account balance. Existing literature either focuses on identifying a set of general determinants of current account without considering oil price or focuses on the effect of oil price for only a single country. This paper fills in the gap by studying the medium-term effect of oil price on the current account of a group of countries using a five-year non-overlapping model developed by Chinn and Ito (2007). This model enables a better characterization of the oil price-current account nexus by reducing the impact of potential measurement errors and eliminating business-cycle fluctuations. Ordinary least squares (OLS) regression is applied on an unbalanced panel dataset consisting of 55 countries with yearly data from 1986 to 2015. All the data are obtained from the World Bank, International Country Risk Guide (ICRG), U.S Energy Information Administration (EIA) and Federal Reserve Economic Data (FRED). A set of determinants of current account is selected as the control variables based on past empirical results, i.e. the fiscal balance, the degree of domestic financial development, initial net foreign assets, economic growth rate, income level, dependency ratios, and the degree of trade openness. There are three main findings in this paper. Firstly, an increase in oil price will only lead to an improvement in the current account of oil-exporting countries. Secondly, the increase in current account is due to an increase in national savings of these countries. Lastly, national investment is not being affected by oil price for both oil-exporting and oil-importing countries.